Are groups really more dishonest than individuals? - Geoffrey Castillo; Lawrence Choo; Veronika Grimm (Friedrich-Alexander-Universität Erlangen-Nürnberg, Institute for Economics, 2020)
A common finding of the literature on dishonesty is that groups are more dishonest than individuals. We revisit this finding by making explicit the third-party harmed by subjects' dishonesty: a local charity. With this explicit third-party, we do not find groups to be more dishonest than individuals. Instead,we find that groups can even help moderate the extent of dishonesty.
Keywords: C91; C92; D71; 330; dishonesty; group decisions; communication; social norms